Pendidikan Anak dalam Al-Qur'an: Kajian Nilai dan Metode Islam - Jutika Fatma (Education Research Center, 2025)
This study aims to explain the position of children from the perspective of the Qur'an and explore educational values ​​and methods that can be applied in developing children's character. The study uses a qualitative-descriptive approach with a literature study type through thematic analysis of Qur'anic verses, classical and contemporary interpretations, as well as Islamic education and developmental psychology literature. The results show that the Qur'an positions children as a trust that must be guarded, a natural disposition that needs to be guided, a trial (slander) for parents, and a comforter. This position provides a theological basis for comprehensive education. The educational values ​​that emerge include faith, worship, morals, and social values ​​as depicted in Luqman's advice to his son. The Qur'anic educational methods found include role models, habituation, advice, and dialogue, all of which are in accordance with the needs of child development. The integration of Jalaluddin Rakhmat's thoughts demonstrates the importance of a humanistic and empathetic approach in Islamic education to avoid being trapped in rigid and normative parenting patterns. This research emphasizes the need for a Qur'anic education model that balances the strength of religious values ​​and an understanding of child psychology so that education can shape character more effectively and relevantly in the modern era